2009
DOI: 10.1080/19338240903348220
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Method for Improving Logistic Regression Estimates under Group-Based Exposure Assessment with Additive Measurement Errors

Abstract: The group-based exposure assessment has been widely used in occupational epidemiology. When the sample size used to estimate group means is "large", this leads to negligible attenuation in the estimation of odds ratio. However, the bias is proportional to the between-subject variability and is affected by the difference in true group means. We explore a Bayesian method, which adjusts in a natural way for the extra uncertainty in the outcome model associated with using the predicted values as exposures. We aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…There is another conclusion from our theoretical calculation, which can be supported by the simulation results mentioned in . Assume that there is the same increment between the adjacent group means.…”
Section: Bias Of the Group‐based Exposure Assessment Methodssupporting
confidence: 61%
See 3 more Smart Citations
“…There is another conclusion from our theoretical calculation, which can be supported by the simulation results mentioned in . Assume that there is the same increment between the adjacent group means.…”
Section: Bias Of the Group‐based Exposure Assessment Methodssupporting
confidence: 61%
“…Assume that there is the same increment between the adjacent group means. Kim and Burystyn inspected the bias and MSE of the estimated β 1 when β 0 = − 4, β 1 = 0.4, and μ 1 = 0.1 and the increment varies as 0.3,0.5,1, and 1.414 in their simulation studies. They concluded that when the increment between groups is large and the between‐subject variance is relatively small, the group‐based exposure assessment method gives unbiased estimates, whereas it fails to adjust for the measurement errors properly when the increment is small.…”
Section: Bias Of the Group‐based Exposure Assessment Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensitivity analyses were conducted with alternative simulated employment durations based on information on employment durations from another, partly overlapping, cohort of British rubber factory workers6 15 29 and showed that results of the main analyses are robust. Although exposure estimates from JEMs are generated from mean exposure values and therefore do not allow for individual variabilities, errors that arise from them tend to be attenuated Berkson-type errors, which, unlike random errors, generally do not bias exposure–response associations 30–32. Finally, exposure-specific estimates of LCE enabled multipollutant models to explore issues of complex exposure mixtures across the production process.…”
Section: Discussionmentioning
confidence: 99%